2021
DOI: 10.1111/1365-2664.13905
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Southeast Asian tropical peatlands and integrated strategies for their better management and restoration

Abstract: 1. About half of the world's tropical peatlands occur in Southeast (SE) Asia, where they serve as a major carbon (C) sink. Nearly 80% of natural peatlands in this region have been deforested and drained, with the majority under plantations and agriculture. This conversion increases peat oxidation which contributes to rapid C loss to the atmosphere as greenhouse gas emissions and increases their vulnerability to fires which generate regional smoke haze that has severe impacts on human health. Attempts at restor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 143 publications
(246 reference statements)
1
32
0
Order By: Relevance
“…In our review, mycorrhizal inoculation enhanced TPSF seedling survival, but not half‐life or RGR. A promising avenue for further research would be investigations into the nutrient acquisition strategies of TPSF species, for example, mycorrhizal symbiosis (Mishra et al, 2021) to develop alternative strategies to the application of artificial fertilisers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our review, mycorrhizal inoculation enhanced TPSF seedling survival, but not half‐life or RGR. A promising avenue for further research would be investigations into the nutrient acquisition strategies of TPSF species, for example, mycorrhizal symbiosis (Mishra et al, 2021) to develop alternative strategies to the application of artificial fertilisers.…”
Section: Discussionmentioning
confidence: 99%
“…Intact TPSF have poor drainage, permanent waterlogging and anaerobic conditions that slow decomposition and lead to the formation of peat, that is, partially decomposed organic matter. Conversion and drainage cause peat oxidation and elevated CO 2 emissions, subsidence (lowering of the peat surface) and flooding, increased risk of fires (particularly during drier El Niño conditions), and a surface vegetation primarily comprised of a dense thicket of sedges and ferns that competes with naturally recolonising trees and planted seedlings (Blackham et al, 2014; Miettinen et al, 2017; Mishra et al, 2021; Page et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the important challenges which affect efforts to restore degraded peatlands are increasing the groundwater level on drained peatlands and the development of economically competitive crop species suitable for paludiculture (Wosten et al 2008;Wichtmann et al 2010;Uda et al 2017;Uda et al 2017;Evans et al 2019;Tan et al 2021). Damage to the peat ecosystem causes disturbance to this diversity (Mishra et al 2021). Tropical peatland degradation generally begins after converting PSF into a nonforest area for agriculture, smallholder plantations, and industrial forest plantations, which is usually accompanied by drainage channel construction.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have indicated huge amounts of carbon emissions into the atmosphere due to peatland deforestation and degradation, draining, and repeated res (Jaenicke et al, 2010;Hooijer et al, 2014;Ballhorn et al, 2009). The removal of above-and below-ground biomass, peat decomposition and oxidation caused by drainage, and peat combustion are all major sources of carbon loss and CO 2 emissions into the atmosphere while the application of N fertilisers on degraded peatland acts as a source of N 2 O emission especially when nitrogen fertilisers have been added to promote agricultural productivity (Mishra et al, 2021;. Tree harvesting by clear-cutting on drained peatland has also been reported to enhance the leaching of dissolved organic C (DOC), dissolved organic N (DON), and mineral N to surface waters and the nearest catchment in a boreal peatland (Könönen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%